Providing safe maternity care under challenging conditions in rural Ethiopia: a qualitative study - Elin Mordal; Ingrid Hanssen; Andargachew Kassa Biratu; Solfrid Vatne (BMC, 2021)
Abstract Background Women's health and the reduction in the global maternal mortality rate is a research priority worldwide. The aim of this study was to investigate the structural conditions that influence the maternity care provided for women in rural Ethiopia. Methods A qualitative descriptive study was conducted, composed of 28 individual in-depth interviews with midwives and women who had given birth during the past 8 months, and observations of maternity care at health centres and a primary hospital. A thematic analysis was conducted. Results The midwives do their utmost to save the lives of mothers and prioritise saving lives over providing compassionate care. Inadequate resources, such as equipment, medicine and water, affect the quality of care they provide for the birthing women. This creates a conflict between the midwives' ideals and what conditions allow them to do. Families and the women's network play important roles in providing care and support to the women who give birth in health facilities. Conclusions Structural conditions make it difficult for Ethiopian midwives in rural areas to provide optimal maternity care. In addition to the availability of professional midwifery care, the expectant mothers' families and networks also tend to provide important support and care. Further studies on how to improve the quality of maternity care from the women's perspective are needed.